The effect of an innovative payment method on inpatient volume and bed resources and their regional distribution: the case of a central province in China - Kunhe Lin; Yifan Yao; Yingbei Xiong; Li Xiang (BMC, 2024)
Abstract Background Since 2020, China has piloted an innovative payment method known as the Diagnosis-Intervention Packet (DIP). This study aimed to assess the impact of the DIP on inpatient volume and bed allocation and their regional distribution. This study investigated whether the DIP affects the efficiency of regional health resource utilization and contributes to disparities in health equity among regions. Methods We collected data from a central province in China from 2019 to 2022. The treatment group included 508 hospitals in the pilot area (Region A, where the DIP was implemented in 2021), whereas the control group consisted of 3,728 hospitals from non-pilot areas within the same province. We employed the difference-in-differences method to analyze inpatient volume and bed resources. Additionally, we conducted a stratified analysis to examine whether the effects of DIP implementation varied across urban and rural areas or hospitals of different levels. Results Compared with the non-pilot regions, Region A experienced a statistically significant reduction in inpatient volume of 14.3% (95% CI 0.061-0.224) and a notable decrease of 9.1% in actual available bed days (95% CI 0.041-0.141) after DIP implementation. The study revealed no evidence of patient consultations shifting from inpatient to outpatient services due to the reduction in hospital admissions in Region A after DIP implementation. Stratified analysis revealed that inpatient volume decreased by 12.4% (95% CI 0.006-0.243) in the urban areas and 14.7% in the rural areas of Region A (95% CI 0.051-0.243). At the hospital level, primary hospitals experienced the greatest impact, with a 19.0% (95% CI 0.093-0.287) decline in inpatient volume. Furthermore, primary and tertiary hospitals experienced significant reductions of 11.0% (95% CI 0.052-0.169) and 8.2% (95% CI 0.002-0.161), respectively, in actual available bed days. Conclusions Despite efforts to curb excessive medical service expansion in the region following DIP implementation, large hospitals continue to attract a large number of patients from primary hospitals. This weakening of primary hospitals and the subsequent influx of patients to urban areas may further limit rural patients' access to medical services. The implementation of the DIP may raise concerns about its impact on health care equality and accessibility, particularly for underserved rural populations.